Glare by Light Emitting Diode (LED) vehicle traffic signals - Ixtaina, Pablo Rubén (2015)
Background: In this paper we analyze devices for traffic signals (traffic lights) with light-emitting diode (LED) technology. Methods: The traditional measurements of luminous intensity were complemented with the luminance analysis of the devices, evaluated for diverse angular fields. Besides, a subjective glare evaluation is presented. In the experience, signals with LEDs directly visible and signals with refractors are compared. Both signals were introduced in the visual field of 30 observers within a perceptive scene that simulated night vision conditions for a driver. The observers were later inquired about the experienced perturbation or discomfort sensation. Results: The obtained results show a significant increase in the punctual luminance as well as an evident perturbation and discomfort for the observers. Conclusions: This effect together with the relatively high degree of coherence of the color lights could result in new kinds of glares not considered in the current standards.